Construction of Rules for Recognizing Landslides Along Highways Induced By Rainfall - Wang, Xiaohe (International Journal of Computer Science and Information Technology, 2024)
After the "7-20" concentrated rainfall, many landslides occurred along the highways in Jiaozuo City, which seriously threatened the transportation safety and brought serious economic losses to the government and the residents along the highways. In order to investigate the development pattern and distribution characteristics of landslides along highways under extreme weather, we took Jiaozuo City Highway as the research object, based on the Sentinel-2 remote sensing data, and on the basis of analyzing the spectral characteristics of landslide hazards, we used the band ratio method to establish the identification rules of loess landslides along highways; based on the topography, geology, human impacts, and meteorological and hydrological selected 11 impact factors, and used geoprospectors to investigate the The driving factors of landslides. The following conclusions and understandings were obtained: (1) a total of 256 landslides along the highway in Jiaozuo City were identified, and the overall identification accuracy of 69.9% was obtained through visual interpretation and on-site research; (2) the ratio of the surface true reflectance of red and green light fused with the slope (>15°) can be used to carry out the identification of landslides in large-scale post-disaster situations; (3) the human activities and topography have a greater impact on landslide development; (4) the identification rule has a greater impact on the development of landslides with similar geological backgrounds. rule is useful for the identification and prevention of landslides along highways in low-hill loess-covered areas with similar geologic backgrounds.